2021
DOI: 10.1002/ece3.7558
|View full text |Cite
|
Sign up to set email alerts
|

Why do Argos satellite tags stop relaying data?

Abstract: Satellite tracking of animals is very widespread across a range of marine, freshwater, and terrestrial taxa. Despite the high cost of tags and the advantages of long deployments, the reasons why tracking data from tags stop being received are rarely considered, but possibilities include shedding of the tag, damage to the tag (e.g., the aerial), biofouling, battery exhaustion, or animal mortality. We show how information relayed via satellite tags can be used to assess why tracking data stop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…To examine this possibility further we analyzed the final locations of all tracked whale sharks in relation to vessel densities. While transmitters can fail and cease transmitting for a number of reasons unrelated to mortality ( 32 , 33 ), we reasoned that normal technical failure or loss of satellite transmitters would 1) occur randomly along a shark’s trajectory rather than 2) being more frequently associated with areas of higher vessel activity. We tested both these possibilities (see Methods ) and found that the overlap of actual last locations of sharks within busiest routes (characterized as ≥90th percentile of unique vessel counts within grid cells; 31 vessels for the 2011 to 2014 annual mean) was greater than for randomly selected potential “last” locations ( n = 348 locations; overlap coefficient, OC = 0.065, P < 0.001, 95% CI: [0.041, 0.042]) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To examine this possibility further we analyzed the final locations of all tracked whale sharks in relation to vessel densities. While transmitters can fail and cease transmitting for a number of reasons unrelated to mortality ( 32 , 33 ), we reasoned that normal technical failure or loss of satellite transmitters would 1) occur randomly along a shark’s trajectory rather than 2) being more frequently associated with areas of higher vessel activity. We tested both these possibilities (see Methods ) and found that the overlap of actual last locations of sharks within busiest routes (characterized as ≥90th percentile of unique vessel counts within grid cells; 31 vessels for the 2011 to 2014 annual mean) was greater than for randomly selected potential “last” locations ( n = 348 locations; overlap coefficient, OC = 0.065, P < 0.001, 95% CI: [0.041, 0.042]) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Foraging site fidelity is either confirmed via traditional capturemark-recapture (CMR) methods using flipper tags and/or satellite tracking. The latter is typically able to detect site fidelity of relative short time periods, typically only up to couple of years, constrained by the limited duration of satellite tracking devices (Hays et al ., 2021). On the other hand traditional CMR studies on (neritic) foraging grounds are able to document individual histories spanning multiple decades (Rees et al ., 2013; Shimada et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For two other individuals, biofouling was not indicative of tag failure, but the decrease in swimming speed might suggest that the turtles could have died due to cold-stunning in winter. The rapid growth of immature loggerhead turtles could also explain a premature tag detachment (Hays et al, 2021), leading to a shorter tag life (mean: 145 ± 152 days, range: 18-679 days) compared to other studies based on adult individuals, e.g., loggerheads retain 50% of their tags for 584 days (Hart et al, 2021). For future deployments, we recommend a careful battery management based on a severe duty cycling to extend tag life in immature individuals (Christiansen et al, 2016).…”
Section: Resident Behavior In European Coastal Watersmentioning
confidence: 97%
“…The algorithm accounted for the Argos quality to predict the daily locations using Argos error ellipses for the tags deployed after 2011, while the location classes (0, 1, 2, 3, A or B) were used for the remaining tags. Following Hays et al (2021) and Hart et al (2021), assessment of tag failure was conducted on the data available using the three following metrics: battery voltage, wet/dry switches and the number of Argos transmissions.…”
Section: Movement Analysismentioning
confidence: 99%